Safety and effectiveness of standardized exercise training in patients with pulmonary hypertension associated with heart failure with preserved ejection fraction (TRAIN-HFpEF-PH): study protocol for a randomized controlled multicenter trial - Eglė Palevičiūtė; Jelena Čelutkienė; Toma Šimbelytė; Lina Gumbienė; Elena Jurevičienė; Diana Zakarkaitė; Sigitas Čėsna; Christina A. Eichstaedt; Nicola Benjamin; Ekkehard Grünig (Trials, 2023)
Abstract Background Left heart failure (HF) is characterized by an elevation in left-sided filling pressures, causing symptoms of dyspnea, impairing exercise capacity, and leading to pulmonary venous congestion and secondary pulmonary hypertension (PH). There is an increased incidence of PH associated with left heart disease, particularly with heart failure with preserved ejection fraction (HFpEF-PH). Treatment possibilities in HFpEF-PH are non-specific and very limited, thus additional pharmacological and non-pharmacological therapeutic strategies are needed. Various types of exercise-based rehabilitation programs have been shown to improve exercise capacity and quality of life (QoL) of HF and PH patients. However, no study focused on exercise training in the population of HFpEF-PH. This study is designed to investigate whether a standardized low-intensity exercise and respiratory training program is safe and may improve exercise capacity, QoL, hemodynamics, diastolic function, and biomarkers in patients with HFpEF-PH. Methods A total of 90 stable patients with HFpEF-PH (World Health Organization functional class II–IV) will be randomized (1:1) to receive a 15-week specialized low-intensity rehabilitation program, including exercise and respiratory therapy and mental gait training, with an in-hospital start, or standard care alone. The primary endpoint of the study is a change in 6-min walk test distance; secondary endpoints are changes in peak exercise oxygen uptake, QoL, echocardiographic parameters, prognostic biomarkers, and safety parameters. Discussion To date, no study has investigated the safety and efficacy of exercising specifically in the HFpEF-PH population. We believe that a randomized controlled multicenter trial, which protocol we are sharing in this article, will add important knowledge about the potential utility of a specialized low-intensity exercise and respiratory training program for HFpEF-PH and will be valuable in finding optimal treatment strategies for these patients. Trial registration ClinicalTrials.gov NCT05464238. July 19, 2022.